The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10384-006-0416-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Progression of Visual Field Damage in Patients with Normal-Tension Glaucoma

Abstract: Reference1. Spaeth GL, Hwang S, Gomes M. Disc damage as a prognostic and therapeutic consideration in the management of patients with glaucoma. In: Gramer E, Grehn F, editors. Pathogenesis and risk factors of glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The role of IOP reduction of <30% from baseline IOP with topical medications is still controversial in NTG patients. Nakagami et al. (2006) reported that IOP reduction via topical medication was effective for prevention of VF progression in patients with NTG.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of IOP reduction of <30% from baseline IOP with topical medications is still controversial in NTG patients. Nakagami et al. (2006) reported that IOP reduction via topical medication was effective for prevention of VF progression in patients with NTG.…”
Section: Discussionmentioning
confidence: 99%
“…However, most previous studies dealing with NTG progression used only VF deterioration as the end‐point (Shigeeda et al. 2002; Nakagami et al. 2006; Seong et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported that lowering intraocular pressure (IOP) slowed the advancement of visual field damage in glaucoma patients. [1][2][3][4][5][6][7][8][9] However, even if the IOP can be substantially lowered, the reduction of mean and peak IOPs does not always prevent visual field progression. [10][11][12] There are several reports that diurnal IOP variation is a risk factor for glaucoma.…”
Section: Introductionmentioning
confidence: 99%